Joint models reveal human subcortical underpinnings of choice and learning behavior - Steven Miletić; Niek Stevenson; Pierre-Louis Bazin; Anneke Alkemade; Scott J. S. Isherwood; Anne C. Trutti; Desmond H. Y. Tse; Asta K. Håberg; Birte U. Forstmann (Proceedings of the National Academy of Sciences, 2025)
Decision making and learning processes together enable adaptive strategic behavior. Animal studies demonstrated the importance of subcortical regions in these cognitive processes, but the human subcortical contributions remain poorly characterized. Here, we study choice and learning processes in the human subcortex, using a tailored ultra-high field 7T functional MRI protocol combined with joint models. Joint models provide unbiased estimates of brain–behavior relations by simultaneously including behavioral and neural data at the participant and group level. Results demonstrate relations between subcortical regions and the adjustment of decision urgency. Value-related blood-oxygenation level dependent (BOLD) differences were found with opposite BOLD polarity in different parts of the striatum. Multiple subcortical regions showed BOLD signatures of reward prediction error processing, but contrary to expectations, these did not include the dopaminergic midbrain. Combined, this study characterizes the human subcortical contributions to choice and learning, and demonstrates the feasibility and value of joint modeling in facilitating our understanding of brain–behavior relationships.